HBV is a risk factor for poor patient prognosis after curative resection of hepatocellular carcinoma: A retrospective case–control study. Issue 31 (August 2016) - Li, Zhonghu; Zhao, Xin; Jiang, Peng; Xiao, Senlin; Wu, Guo; Chen, Kai; Zhang, Xi; Liu, Hui; Han, Xiuguo; Wang, Shuguang; Li, Xiaowu
Abstract : Abstract: Controversy exists regarding pathological factors affecting the prognosis of hepatocellular carcinoma (HCC) patients with hepatitis B virus (HBV-HCC). Their postoperative clinical behaviors and the exact HBV Deoxyribonucleic Acid (DNA) thresholds that distinguish good and poor prognoses are unknown. This study aimed to compare clinicopathological, pre- and postoperative clinical factors and overall and recurrence-free survival (RFS) between HBV-HCC patients and nonhepatitis B and nonhepatitis C HCC (NBC-HCC) patients to determine the optimal prognostic HBV DNA threshold. Data from 1440 patients with HBV-HCC and NBC-HCC who underwent curative hepatectomy were retrospectively analyzed. Liver function in the HBV-HCC group was significantly worse than in the NBC-HCC group. Compared with NBC-HCC patients, HBV-HCC patients had significantly more vascular invasion and advanced HCC. The HBV-HCC patients also had significantly worse liver function and more complications. Further survival analysis showed significantly lower overall and RFS rates and a higher early recurrence rate in the HBV-HCC group. Univariate analysis indicated that HBV was a risk factor for overall and RFS. Finally, X-tile analysis revealed that the optimal HBV DNA cutoff points for predicting RFS and overall survival in HCC patients were 10, 100 and 12, 800 IU/mL, respectively. After hepatectomy for HCC, HBV-HCC patients had more complications and a worse prognosis than NBC-HCC patients. Antiviral therapy should be considered before hepatectomy in patients with high (more than approximately 10 4  IU/mL) HBV DNA levels. Abstract : Supplemental Digital Content is available in the text